Single dose pharmacokinetic equivalence study of two gabapentin preparations in healthy subjects - Tjandrawinata, Raymond; Setiawati, Effi; Putri, Ratih S.I.; Yunaidi, Danang A.; Amalia, Fawzia; Susanto, Liana W. (Drug design, development and therapy, 2014)
The current study was conducted to find out whether two oral preparations of 300 mg gabapentin (the test and reference capsules) were bioequivalent. This was a randomized, single-blind, crossover study under fasting condition, with a 7-day washout period, which included 37 healthy adult male and female subjects. After an overnight fast, subjects were given, orally, one capsule of the test drug or of the reference drug. Blood samples were drawn immediately before taking the drug, then at 20 and 40 minutes, and 1, 1.5, 2, 2.5, 3, 4, 5, 6, 8, 10, 12, 15, and 24 hours after dosing, to evaluate pharmacokinetic parameters of the single dose administration, ie, the area under the plasma concentration-time curve (AUC) from time zero to 24 hours (AUCt), AUC from time zero to infinity (AUC(inf)), the peak plasma concentration of the drug (Cmax), time needed to achieve Cmax (tmax), and the elimination half-life (t1/2). The plasma concentrations of gabapentin were determined using validated high-performance liquid chromatography with ultraviolet detection. The geometric mean ratios (90% confidence interval) of the test drug/reference drug for gabapentin were 103.15% (90.38%-117.72%) for AUCt, 103.53% (90.78%-118.07%) for AUC(inf), and 108.06% (96.32%-121.24%) for Cmax. The differences in tmax and t1/2 values between the test and reference drug products for gabapentin were not statistically significant. Light-headedness, nausea, and headache were encountered during the study, but they were all mild and well tolerated. The 90% confidence intervals of the test/reference AUC ratio and Cmax ratio of gabapentin were within the acceptance range for bioequivalence. The two preparations of gabapentin 300 mg capsule were bioequivalent, thus both can be used interchangeably in the clinical setting.